Changes in body size and body composition in survivors of childhood cancer: seven years follow-up of a prospective cohort study. Issue 12 (December 2022) - Brinksma, Aeltsje; Sulkers, Esther; Kouwenberg, Dorus; Lelieveld, Otto T.H.M.; Boot, Annemieke M.; Burgerhof, Johannes G.M.; Tissing, Wim J.E.
Summary: Background & aims: Cancer treatment is known to have impact on nutritional status, and both underweight and overweight have been reported in several studies in survivors. A limitation of most studies is that they relied on retrospective data or were limited to a subgroup of patients. The current study aims to describe changes in body size and body composition prospectively seven years after diagnosis in a heterogeneous sample of childhood cancer survivors and to evaluate associated factors. Methods: The study population consisted of children diagnosed with hematological, solid and brain malignancies aged 0–18 years at diagnosis. Data of body size, body composition, and associated factors were collected at diagnosis, one year and seven years after diagnosis. Results: In the total cohort mean BMI z-score increased during treatment. In children with hematological and brain malignancies BMI z-score continued to increase after end of treatment leading to quadrupling of the prevalence of obesity seven years after diagnosis. BMI at diagnosis (β = −0.34, P  = 0.007) and maternal BMI (β = 0.25, P  = 0.046) were associated with the increase in BMI z-score. Mean fat mass (FM) z-score, already high at diagnosis, increased during treatment in children with hematological and brain malignancies and evened out during follow-up. Changes in FM z-score were predicted by type of malignancy (hematologic malignancy versus solid tumor β = 0.48, P  = 0.008; brain tumor versus solid tumor β = 0.45, P  = 0.012). Mean fat free mass (FFM) z-scores started low at diagnosis, particularly in patients with brain tumors, increased during treatment in patients with solid and brain malignancies, though decreased in children with hematological malignancies. At 7 years follow-up a clear increase to normal was seen. Age at diagnosis (β = 0.43, P  = 0.004) and initial FFM (β = −0.49, P  = 0.001) were found to be significant predictors for changes in FFM z-scores. Conclusions: The finding that the once obtained extra weight and FM during treatment persisted after termination of treatment in children with hematological and brain malignancies, stresses the importance to create awareness about the risk of developing overweight in children during cancer treatment.